Analysis of Clinical, Imaging, and Pathologic Features of 36 Patients with Primary Intraspinal Primitive Neuroectodermal Tumors: A Case Series and Literature Review - Wei, Xuefeng; Zhang, Xu; Song, Zimu; Wang, Feng (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Study Aims Primary intraspinal primitive neuroectodermal tumors (PNETs) account for ∼0.4% of all intraspinal tumors, but information about these tumors in the medical literature is limited to single case reports. We report four cases of primary intraspinal PNETs and present a systematic literature review of the reported cases.Materials and Methods We retrospectively reviewed and analyzed the clinical data of 4 patients with primary intraspinal PNETs who underwent neurosurgical treatment at our clinic between January 2013 and January 2020, and of 32 cases reported in the literature.Results The female-to-male ratio was 2.6:1. The mean patient age was 21.42 ± 15.76 years (range: 1–60 years), and patients <36 years of age accounted for 83.30% of the study cohort. Progressive limb weakness and numbness were the chief symptoms (accounting for ∼55.6%). The mean complaint duration was 0.89 ± 0.66 months for males and 2.72 ± 3.82 months for females (p = 0.028). Epidural (41.7%) was the most common site, and thoracic (47.3%) was the most frequent location. Most PNETs were peripheral, and magnetic resonance imaging (MRI) appearance was isointense or mildly hypointense on T1-weighted images and hyperintense on T2-weighted images. Homogeneous contrast enhancement was observed. The 1-year survival rate of patients who underwent chemoradiation after total or subtotal lesion resection was better compared with patients who did not undergo chemotherapy, radiotherapy, or total or subtotal resection. The modality of treatment was associated with survival time (p = 0.007).Conclusion Primary intraspinal PNETs mainly occur in young people with a female preponderance. In patients with a rapid loss of lower limb muscle strength and large intraspinal lesions on MRI, PNETs should be considered. Surgical resection and adjuvant radio chemotherapy are key prognostic factors.
Keywords: primitive neuroectodermal tumors; intraspinal; clinical manifestation; prognosis